Choice under uncertainty and cognitive load - Adam Dominiak; Peter Duersch (Journal of Risk and Uncertainty, 2024)
Does exposure to cognitive load affect key properties of economic behavior? In this experiment, subjects face a series of simple binary decision tasks between prospects, testing for monotonicity in monetary payments, consistency with (first-order) stochastic dominance, reduction of compound lotteries, risk attitudes, and ambiguity attitudes. Cognitive load is manipulated via simultaneous memory tasks. Our data show treatment differences resulting from cognitive load for decision tasks with risky outcomes. However, cognitive load has no impact on monotonicity and ambiguity attitudes. Under a dual-process view of human decision-making, our findings suggest that ambiguity attitudes and preferences for “more certain money” are intuitive, not reasoned.
Keywords: C91; D81; D91; 300; Cognitive load; Certainty; Risk; Ambiguity; Cognitive ability; Experiment